GAMBANG DI SUNDA - S.Sen.,M.Sn., Soleh (Paraguna, 2018)
Gambang  in Sunda   consists of Gambang  that  is  native  to the  Sunda region  and originating from outside  the  Sunda region.  The  existence of the  original  Gambang from  the  Sunda   region  was  pressured  by  the  existence of Gambang   originating from  outside   the  Sunda  region.  This  is  due  to  the  existence  of the  people  who became  the central.figure  who  encouraged the growing popularity  of the xylophone from outside  Sunda  with  the existence of the gamelan  salendro.